PENGARUH MEDIA PEMBELAJARAN KAHOOT TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS X SMAS PARULIAN 1 MEDAN TAHUN AJARAN 2025/2026 - Iindola Simbolon; Dearlina Sinaga; Nova Yunita Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the use of Kahoot learning media on the economics learning outcomes of class X students of Parulian 1 Private High School Medan in the 2025/2026 Academic Year. The background of this study is based on the low learning outcomes of students who have not reached the Minimum Completion Criteria (KKM) and the still limited use of technology-based learning media in the learning process. This study uses a quantitative approach with a pre-experimental design through a one group pretest–posttest design. The population in this study were all class X students of Parulian 1 Private High School Medan, totaling 86 students, while the research sample was 28 class X-3 students selected using a purposive sampling technique. Data collection techniques were carried out through tests, observations, questionnaires, and documentation. Data analysis was carried out by means of analysis prerequisite tests in the form of normality tests, hypothesis tests using paired sample t-tests and N-Gain tests with the help of the SPSS program. The results of the study showed that the average pretest score of students was 56.96, while the average posttest score was 82.50, which indicated an increase in learning outcomes after the use of Kahoot learning media. The results of the hypothesis test showed a t-value of -13,000 with a significance value of 0.000 <0.05, so H0 was rejected and H1 was accepted. In addition, the N-Gain test showed a value of 57.5% which was in the moderate category. This indicates that there is a significant influence between student learning outcomes before and after the use of Kahoot learning media. Thus, it can be concluded that the use of Kahoot learning media has a significant effect on improving the economic learning outcomes of class X students of SMA Swasta Parulian 1 Medan.